Assessment of Kuku Dairy Cooperative Production System in Sudan - Musa, Lutfi Mohamed-Ahmed; Omer, Samah Khalafalah Mohamed; Alkhider, Sara Omer Ibrahim (Journal of Veterinary Medicine and Animal Production, 2021)
This study was conducted in 2010 to assess the current situation of Kuku Dairy Cooperative, looking for possible opportunities to promote the cooperative with a view to the development of a community-based improvement breeding programme. A set of detailed semi-structured questionnaires were used to collect information from 56 cooperative members in one-visit-interviews. The members kept different species of animals, but cattle were the dominant and most important. Almost all cattle were crossbreds (Kenana or Butana with Friesian) with different levels of foreign blood. Seventy three percent of the members were educated and aware of the importance of the collective action in reducing the production costs and enhancing the production conditions. Obtaining services was the main purpose for joining Kuku Dairy Cooperative.However, the members considered ownership of agricultural land (31.7%), milk marketing (21.1%), agricultural inputs (21.1%) and veterinary services (16.3%) to be the primary reasons for joining the cooperative. Recently, the Cooperative’s activities and services were influenced by inadequacy of funds provided by the central government, especially, during the last few decades which witnessed the liberalization of the Sudanese economy and suspension of foreign technical and financial aids by traditional donors. Nearly half of the members (48%) did not participate in electing the executive committee’s members, because they were not satisfied with the governancestructure of the cooperative. Moreover they thought that the committee was monopolized by a group of old members who were elected on the grounds of their status in the community and not on the basis of their dairy farming skillsor commercial insight. The individual farm herd size was quite small (113 ± 53 head), and not conducive for achievement of measurable genetic gain which requires the formation of group breeding schemes, that will require the full participation and long- term commitment of the members. Though almost all the members cultivate fodder, the majority stressed that the expenses for feed, in addition to irrigation fees, market and health care expenses to be the most important limiting factors for dairying. Measures designed to overcome these production constraints can only be implemented if the Kuku Dairy Cooperative becomes more functional. With government support, the members can create their own linkage system, infrastructure of marketing and production support services (e.g. animal breeding, recording system, health care, feed, other inputs and credit facilities).